Hospital admission and vaccination as predictive factors of long COVID-19 symptoms - Romero-Rodríguez, Esperanza; Pérula-de Torres, Luis Ángel; Castro-Jiménez, Rafael; González-Lama, Jesús; Jiménez-García, Celia; González-Bernal, Jerónimo J.; González-Santos, Josefa; Vélez-Santamaría, Rodrigo; Sánchez-González, Esteban; Santamaría-Peláez, Mirian (Frontiers in Medicine, 2022)
Background Since the beginning of the COVID-19 pandemic, a great variability of symptoms that affect all organs and systems of the body has been identified in patients with SARS-CoV-2 infection; this symptomatology can sometimes persist over time, giving rise to the so-called long COVID or post-COVID. The aim of this study is to delve into the clinical characterization of these patients, as well as to take into account the influence of factors such as hospitalization, admission to ICU, history of pneumonia, or vaccination status on the persistence of symptoms. Material and methods An observational, descriptive, multicenter, and retrospective study was designed with a series of cases of people who presented long COVID, which includes univariate, bivariate, and multivariate analyses. Data were obtained from an online ad hoc questionnaire, and statistical analysis was performed using SPSS Software Version 25 (IBM-Inc., Chicago, IL, USA). Results Hospitalization, ICU admission, history of pneumonia, and vaccination were predictive factors (positive or negative) for the following long-COVID symptoms: headache, menstrual disorders, joint pain, cough, chills, nasal congestion, back pain, abdominal pain, weight loss, eye discomfort, facial erythema, itching, tremors, dizziness, seizures, sleeping difficulty, dry eyes, palpitations, fatigue, paresthesia, dyspnea, aphonia, chest pain, high blood pressure, vomiting, memory loss, brain fog, hypothermia, low blood pressure, sputum or phlegm, lack of concentration, hair loss, and erectile dysfunction. Conclusion This study provides evidence on the clinical characterization of patients suffering from long COVID in order to offer them the most appropriate treatments.